PEMETAAN AREA PELAYANAN DAN JARINGAN PT. PLN (PERSERO) DISTRIBUSI JAWA TIMUR BERDASARKAN GOLONGAN PELANGGARAN PELANGGAN - Akbar, Muhammad Sjahid Akbar Sjahid; Amin, Saiful (MATEMATIKA, 2005)
PT. PLN (Persero) East Java Distribution (PLN Jatim) is one of the biggest providing electrics companies in East Java. Electrics is very important need  for people. If PLN experiences some financial losses, then the society will sufter from the impact. One of the causes of PLN losses is the illegal usage of the electricity by some customers.  PLN Jatim has recorded five categories of cutomer violation. The research aimed is to know the position of service area and the network (APJ) based on the violation category. This research uses Cross Tabulation Analysis method and Correspondence Analysis method. The Result shows that Malang and Situbondo’s APJs tend to be A violation category. Mojokerto and Kediri’s APJs tend to be B violation category Banyuwangi, Jember and Pamekasan’s APJs tend to be C violation category. Madiun, Pasuruan and Sidoarjo’s APJs tend to be D violation category. Gresik’s APJs tend to be E violation category.